Unitarization of Schur representations of a partially ordered set associated with $\widetilde{E}_7$ - Yakymenko, D. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We prove that every Schur representation of a partially ordered set associated with graph $\widetilde{E}_7$ can be unitarized with some character.